Polarised discourse of complaint management: ideological construction of the GST in Malaysian online news articles - Ong, Cheng Teik; Hajar Abdul Rahim; Kumaran Rajandran (Penerbit Universiti Kebangsaan Malaysia, 2023)
The introduction of the Goods and Services Tax (GST) in Malaysia signals a significant achievement in the reform of the country’s tax system. An important feature of the tax implementation is the provision of a complaint management mechanism in defusing potentially explosive issues. In response to the negative perception of the tax, the Barisan Nasional (BN) government began a nationwide educational campaign in 2010 to clarify perceived misinformation about the tax. This led to the setting up of the GST Malaysia Info website with an archive of positive news articles by the pro-government mainstream media. This article focuses on the articulation of the discourse of complaint management to examine how the government negotiated the GST by addressing GST complaints to avert viral online postings. Predicated on Fairclough’s three-dimensional Critical Discourse Analysis framework focusing on the experiential value of formal linguistic features of overlexicalisation andcategorisation, this article investigates the perpetuation of an ideological polarisation in favour of the government through the discourse of complaint management. This study seeks to draws attention to the instrumental role of language in projecting a limited aspect of reality through the text producers’ subjective lens. The findings have potential implications for teaching by informing teachers’ text selection for enrichment reading activities to improve students’ knowledge on a particular issue, partisan reporting of the mainstream media and the ideological investment of the text producers, among others. In the larger educational context, this research provides a way in which critical literacy can be incorporated into language syllabus to promote 21st century skills and competencies.